Efficacy and safety of electroacupuncture in patients with postpartum depression: a meta-analysis - Fang, Xue; Wang, Xiaoyan; Zheng, Wenjun; Han, Jing; Ge, Xiaobin (Frontiers in Psychiatry, 2024)
Objective: This study aimed to assess the clinical effectiveness and safety of electroacupuncture (EA) for the treatment of postpartum depression (PPD).We systematically retrieved relevant randomized controlled trials (RCTs) from electronic databases, including PubMed, Cochrane Library, China National Knowledge Infrastructure, EMBASE, China Science and Technology Journal Database, Chinese Biological Medical Database, and the Wanfang database from their inception to November 2023. The outcomes measured were the Hamilton Depression Rating Scale (HAMD) scores, Edinburgh Postnatal Depression Scale (EPDS) scores, adverse events (AEs), and the total response rate. The study aimed to estimate heterogeneity, publication bias, mean difference (MD), and risk ratios (RR) with 95% confidence intervals (CIs).Results: This study included 12 RCTs with a total of 1364 participants (571 in the treatment group and 793 in the control group) for analysis. The results of the meta-analysis indicated that EA did not significantly reduce HAMD (MD = 1.49, 95% CI = [-0.30, 3.27], P = 0.1, I 2 = 0%) and EPDS (MD = 1.12, 95% CI = [-1.62, 3.85], P = 0.42, I 2 = 32%) scores compared to sham EA among patients with PPD, resulting in low heterogeneity. In terms of the total response rate, the EA group exhibited superior results compared to the placebo group (RR = 1.77, 95% CI = [1.15, 2.74], P = 0.01, I 2 = 0%) and the sham EA group (RR = 1.2, 95% CI = [1.02, 4.4], P = 0.02, I 2 = 0%), with statistical significance and low heterogeneity. The incidence of AEs was lower, also with low heterogeneity (RR = 0.9, 95% CI = [0.57, 1.43], P = 0.66, I 2 = 12%).The current evidence indicates that the effectiveness and safety of EA in the treatment of PPD warrant affirmation. However, EA does not demonstrate superiority over sham EA in reducing HAMD and EPDS scores in patients with PPD.Due to the limited quantity and quality of curent research, the above conclusion should be further validated through high-quality studies to confirm the efectiveness of EA in PPD management.